Notes on two species of the genus Fairmairoplia (Coleoptera: Scarabaeidae: Melolonthinae: Hopliini) from Madagascar - Vasko, B. M. (The Kharkiv Entomological Society Gazette, 2026)
New records for Fairmairoplia carinata Lacroix, 1997 and F. compacta Lacroix, 1997 in Madagascar are given. On the basis of the available material, the description of F.  carinata, based on a single specimen from Eastern Madagascar, has been supplemented. 7 figs, 1 refs.
Keywords: Monkey beetles; Afrotropical realm; diagnoses; new location; taxonomy; morphology